PENGARUH PERBEDAAN PERSENTASE PENAMBAHAN SUSU FULL CREAM TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK ES KRIM BERAS MERAH - Bakti, Andrea Tania; Surjoseputro, Sutarjo; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2017)
Red rice is a type of rice that is generally consumed by milling into red rice with husk still attached to the endosperm. In recent years the consumption of red rice in Indonesia begin increase and is popularized as a healthy lifestyle. One type of product that can be extended the use of red rice is red rice ice cream. Besides its high nutrition, red rice ice cream has a distinctive advantage of anthocyanin and also contains red rice flavor that characterizes the product. Ice cream has a creamy taste, easily melts in the mouth and soft texture. The texture is influenced by the presence of fat in the ice cream which helps to trap air (whipping process) that affect the amount and size of ice crystals formed. In this study the making of red rice ice cream is using red rice milk with a very small fat content in (1-2.9%), causing some differences in the physical and organoleptic properties of the ice cream. To help improve the texture of ice cream, the addition of full cream milk with a concentration of 8-13% is needed. The experimental design uses Randomized Block Design (RBD) which will be replicated five times for each treatment. Parameters that will be analysed in this study are the physicochemical parameters and organoleptic, including overrun percentage, hardness, melting rate, and organoleptic characteristics (texture, taste, flavor). Obtained data will be statistically analyzed to determine whether there are significant differences in the percentage of full cream milk powder to the parameters using ANOVA (Analysis of Variance) at α = 5%. If there is a significance difference, then it will be continued with DMRT (Duncan’s Multiple Range Test) at α = 5% to determine which treatments were significantly different. The addition of full cream milk affect the overrun percentage, hardness, melting rate , and organoleptic characteristics (texture, flavor, taste) . The study result shows that overrun percentage is 16.58-22.77% and hardness is 89.07-1191.01 gram. The most preffered treatment is the addition of 13% full cream milk.